2010
DOI: 10.3945/jn.110.126359
|View full text |Cite
|
Sign up to set email alerts
|

Biotin Regulates the Expression of Holocarboxylase Synthetase in the miR-539 Pathway in HEK-293 Cells

Abstract: Holocarboxylase synthetase (HCS) catalyzes the covalent binding of biotin to carboxylases and histones. In mammals, the expression of HCS depends on biotin, but the mechanism of regulation is unknown. Here we tested the hypothesis that microRNA (miR) plays a role in the regulation of the HCS gene. Human embryonic kidney cells were used as the primary model, but cell lines from other tissues and primary human cells were also tested. In silico searches revealed an evolutionary conserved binding site for miR-539 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…However, to our knowledge, only three reports have described the function of miR-539. Firstly, one study found that miR-539 is among the factors sensing cellular biotin levels and targets holocarboxylase synthetase (HCS) [18]. Secondly, miR-539 has been reported to suppress O-GlcNAcase expression and to play an important role in the failing heart [19].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…However, to our knowledge, only three reports have described the function of miR-539. Firstly, one study found that miR-539 is among the factors sensing cellular biotin levels and targets holocarboxylase synthetase (HCS) [18]. Secondly, miR-539 has been reported to suppress O-GlcNAcase expression and to play an important role in the failing heart [19].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…(b) The human HLCS promoter has been tentatively identified (Warnatz et al 2010) but not yet characterized in great detail. (c) The expression of HLCS is repressed by miR-539 (Bao et al 2010). (d) HLCS-dependent histone biotinylation cross talks with cytosine methylation in gene regulation.…”
Section: Biotinylation Of Histonesmentioning
confidence: 99%
“…Additionally, it was found that the expression of the holocarboxylase synthetase enzyme responsible for attaching biotin to the carboxylases is regulated by miR-539 and miR-153 [45,46]. …”
Section: Effect Of Macro- and Micronutrients On Mirna Expressionmentioning
confidence: 99%
“…Biotin deficiency (vitamin H or vitamin B 7 ) has been shown to alter carbon metabolism gene expression in three different eukaryotes (yeast, worm, and rat [44]), and a decrease in the expression of miR-539 is observed under these circumstances [45]. Additionally, it was found that the expression of the holocarboxylase synthetase enzyme responsible for attaching biotin to the carboxylases is regulated by miR-539 and miR-153 [45,46].…”
Section: Effect Of Macro- and Micronutrients On Mirna Expressionmentioning
confidence: 99%